Genetics and mapping of a new anthracnose resistance locus in Andean common bean Paloma - Sandra Aparecida de Lima Castro; Maria Celeste Gonçalves-Vidigal; Thiago Alexandre Santana Gilio; Giselly Figueiredo Lacanallo; Giseli Valentini; Vanusa da Silva Ramos Martins; Qijian Song; Marta Zulema Galván; Oscar P. Hurtado-Gonzales; Marcial Antonio Pastor-Corrales (BMC Genomics, 2017)
Abstract Background The Andean cultivar Paloma is resistant to Mesoamerican and Andean races of Colletotrichum lindemuthianum, the fungal pathogen that causes the destructive anthracnose disease in common bean. Remarkably, Paloma is resistant to Mesoamerican races 2047 and 3481, which are among the most virulent races of the anthracnose pathogen. Most genes conferring anthracnose resistance in common bean are overcome by these races. The genetic mapping and the relationship between the resistant Co-Pa gene of Paloma and previously characterized anthracnose resistance genes can be a great contribution for breeding programs. Results The inheritance of resistance studies for Paloma was performed in F2 population from the cross Paloma (resistant) × Cornell 49–242 (susceptible) inoculated with race 2047, and in F2 and F2:3 generations from the cross Paloma (resistant) × PI 207262 (susceptible) inoculated with race 3481. The results of these studies demonstrated that a single dominant gene confers the resistance in Paloma. Allelism tests performed with multiple races of C. lindemuthianum showed that the resistance gene in Paloma, provisionally named Co-Pa, is independent from the anthracnose resistance genes Co-1, Co-2, Co-3, Co-4, Co-5, Co-6, Co-12, Co-13, Co-14, Co-15 and Co-16. Bulk segregant analysis using the SNP chip BARCBean6K_3 positioned the approximate location of Co-Pa in the lower arm of chromosome Pv01. Further mapping analysis located the Co-Pa gene at a 390 kb region of Pv01 flanked by SNP markers SS82 and SS83 at a distance of 1.3 and 2.1 cM, respectively. Conclusions The results presented here showed that Paloma cultivar has a new dominant gene conferring resistance to anthracnose, which is independent from those genes previously described. The linkage between the Co-Pa gene and the SS82 and SS83 SNP markers will be extremely important for marker-assisted introgression of the gene into elite cultivars in order to enhance resistance.